2015
DOI: 10.1039/c5dt03335g
|View full text |Cite
|
Sign up to set email alerts
|

Stability and toxicity of tris-tolyl bismuth(v) dicarboxylates and their biological activity towards Leishmania major

Abstract: A series of 29 tris-tolyl bismuth(v) di-carboxylato complexes of composition [Bi(Tol)3(O2CR)2] involving either ortho, meta or para substituted tolyl ligands have been synthesized and characterised. Of these 15 were assessed for their toxicity towards Leishmania promastigotes and human fibroblast cells, with ten then being subsequently assessed against parasite amastigotes. The carboxylate ligands are drawn from a series of substituted and biologically relevant benzoic acids which allow a comparison with earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…It was observed that even after 72 hr, a very minute quantity of the decomposition products, whose identity is unknown, settled at the bottom as white precipitate. The studies demonstrate broader stability spectrum for such type of compounds as earlier reports revealed …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It was observed that even after 72 hr, a very minute quantity of the decomposition products, whose identity is unknown, settled at the bottom as white precipitate. The studies demonstrate broader stability spectrum for such type of compounds as earlier reports revealed …”
Section: Resultssupporting
confidence: 82%
“…The other characteristic IR absorption bands observed are; 470–495 and 420–450 cm −1 corresponding to C‐Bi out of plane deformations and Bi‐O stretching mode vibrations which are consistent with the literature values . The Δν (νCO 2 asymm − νCO 2 symm ) values fall in range 150–250 cm −1 depicting that the carboxylato ligands adopt a bidentate or anisobidentate binding mode for ( 1 – 7 ) as earlier reports manifested and further authentication came through crystallographic data . The NMR spectra of the complexes show a high frequency shift in 1 H and 13 C resonances for the carboxylate moiety relative to those observed for free acids.…”
Section: Resultsmentioning
confidence: 71%
“…17,18 Accordingly, several metal complexes have been investigated against CD and leishmaniasis. 4,[19][20][21] The combination of metal ions with drugs and organic ligands can enhance their activity while at the same time, reducing the toxicity and undesired side effects that metal ions on their own could impart. [22][23][24] In this study, the synthesis of a series of amino-and iminopyridyl ligands and some of their metal complexes is reported.…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 value of 37 against L. major promastigotes was 0.71 μM and the IC 50 value against fibroblast cells was 2.95 μM, affording a selectivity index (SI) of 4.15. The antiparasite activity of 38 (IC 50 =0.76 μM) remained similar to that of 37 whereas the undesirable cytotoxicity against human fibroblast cells decreased (IC 50 =11.96 μM) . The SI of tris‐tolyl derivative 38 was 15.7 illustrating how methylation can improved a molecule's pharmacological characteristics .…”
Section: Organometallic Acetylsalicylic Acid (Aspirin) Derivativesmentioning
confidence: 89%